Deciphering sevoflurane-induced neurotoxicity: from isolated targets to intricate regulatory networks - Shu, Yue; Bai, Liang; Yu, Shouyang; Li, Yulan (Frontiers in Neuroscience, 2025)
Among the 321 million surgeries performed globally each year, sevoflurane dominates the inhaled anesthesia field due to its unique pharmacological properties. However, studies indicate that sevoflurane exerts multiple adverse effects on the nervous system, and its potential neurotoxic effects are increasingly drawing attention. This article integrates multi-level evidence from molecular mechanisms, cellular models, animal experiments, and clinical studies to comprehensively elucidate the key mechanisms underlying sevoflurane-induced neurotoxicity, including ferroptosis pathway activation, calcium homeostasis disruption, BDNF signaling abnormalities, neuroinflammatory responses, and endoplasmic reticulum stress. The findings aim to provide a theoretical foundation for developing precise neuroprotective strategies and optimizing clinical anesthesia protocols.